MEDICATION ADHERENCE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - A CROSS-SECTIONAL STUDY - PRATHYUSHA RANI T,; PRASHANTHI B,; AYESHA AMREEN FATHIMA,; AYESHA FIRDOSE,; SARA NASER,; NAJMA BEGUM,; KAUSER BEGUM, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: This study was conducted to determine the adherence of medications among type 2 diabetes mellitus (DM) patients. To evaluate adherence to therapy and study factors associated with non-adherence and adherence in patients with type II DM. Methods: A cross-sectional, observational study was conducted for 6 months in three hospitals. A total of 200 type II diabetic patients, who were on anti-diabetic drug therapy for at least 6 months, were enrolled. Blood glucose was measured and details of drug therapy were noted. Medication adherence was assessed using the Morisky Medication Adherence Scale and adherence scores were calculated. Results: Only 15% had high medication adherence, while 24% had moderate and 61% had low medication adherence. Only 30% were having optimally controlled glycemic levels, whereas 70% were having uncontrolled glycemic levels. Medication adherence scores were lower (reflecting lower adherence) in type II patients with uncontrolled glycemic levels than those having optimally controlled glycemic levels, but this difference was not statistically significant. Conclusion: Overall, medication adherence was low in type II diabetic patients. The study shows that to improve medication adherence, better counseling and health education of patients are required. Although several patients were adherent to therapy, adherent patients are more preferably to achieve glycemic control than nonadherent patients. Greater efforts are needed to facilitate diabetes self-management behaviors to improve patient outcomes.